2022
DOI: 10.1093/milmed/usac144
|View full text |Cite
|
Sign up to set email alerts
|

Acute Fatigue Responses to Occupational Training in Military Personnel: A Systematic Review and Meta-Analysis

Abstract: Introduction Military personnel are required to undertake rigorous physical training to meet the unique demands of combat, often leading to high levels of physiological stress. Inappropriate recovery periods with these high levels of physical stress may result in sub-optimal training and increased risk of injury in military personnel. However, no reviews have attempted to examine the magnitude of training-induced stress following military training activities. The aim of this systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…However, if it had been removed, the pooled effect size value of maximal jumping height or distance would have changed from 0.46 (− 0.59 to 1.52) to 0.00 (− 0.21 to 0.21) and, I 2 value from 95.2 to 0.0%. Several studies have reported decrements in lower body power after strenuous military field exercise 15,58 . This may be due to neuromuscular fatigue combined with loss of muscle mass, the two factors contributing to fast force production ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if it had been removed, the pooled effect size value of maximal jumping height or distance would have changed from 0.46 (− 0.59 to 1.52) to 0.00 (− 0.21 to 0.21) and, I 2 value from 95.2 to 0.0%. Several studies have reported decrements in lower body power after strenuous military field exercise 15,58 . This may be due to neuromuscular fatigue combined with loss of muscle mass, the two factors contributing to fast force production ability.…”
Section: Discussionmentioning
confidence: 99%
“…Acute physical fatigue deteriorate cognitive function, physical performance and critical combat skills such as shooting accuracy [7][8][9][10][11] . In general, dramatic short-term hormonal disturbances and negative changes in body composition as well as physical performance have been reported following demanding military field training 3,[12][13][14][15] .…”
Section: Systematic Review and Meta-analysis Applyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Military operations’ demanding endurance requirements underscore the need for elevated cardiovascular fitness. Robust studies have consistently demonstrated that endurance training enhances soldiers’ aerobic capacity and equips them to execute prolonged physical activities with heightened efficiency [ 74 ].…”
Section: Peak Of Performance: the Tactical And Hybrid Training And At...mentioning
confidence: 99%
“…After being admitted, recruits undergo military training that involves a variety of activities, such as technical learning of the equipment to be used, exhaustive physical training, and technical tactical testing, among other practices. The purpose of this stage is to raise the military to physical stress so that in combat conditions he can adequately respond to operational demands (Orr et al, 2020;Heilbronn et al, 2022). Thus, instruction and physical training is, therefore, one of the pillars of the basic training protocol of all military personnel (Heinrich et al, 2012;Orr & Pope, 2015).…”
Section: Introductionmentioning
confidence: 99%